(untitled) (Global Journal of Management and Business Research, 2012)
Iran is the biggest producer of natural gas. The most significant energy development project in Iran is South Pars field which is the biggest natural gas field of world. Capital asset pricing model (CAPM) is a famous model for measuring relation between risk and return. In this paper we extract systematic risk ( #x3B2; ) of South Pars project which cannot be diversified away.